2009
DOI: 10.1603/022.038.0404
|View full text |Cite
|
Sign up to set email alerts
|

Managing Japanese Barberry (Ranunculales: Berberidaceae) Infestations Reduces Blacklegged Tick (Acari: Ixodidae) Abundance and Infection Prevalence WithBorrelia burgdorferi(Spirochaetales: Spirochaetaceae)

Abstract: In many Connecticut forests with an overabundance of white-tailed deer (Odocoileus virginianus Zimmermann), Japanese barberry (Berberis thunbergii DC) has become the dominant understory shrub, which may provide a habitat favorable to blacklegged tick (Ixodes scapularis Say) and white-footed mouse (Peromyscus leucopus Rafinesque) survival. To determine mouse and larval tick abundances at three replicate sites over 2 yr, mice were trapped in unmanipulated dense barberry infestations, areas where barberry was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 33 publications
0
54
1
Order By: Relevance
“…16 Adult ticks were collected in October through December of 2008, 2010, and 2011, and during April and May in 2011, and March and April in 2012. Host-seeking nymphs were collected by the same procedure described for adult ticks during May and June 2008 from two locations in Fairfield, two locations in Middlesex, and three locations in New London Counties, Connecticut.…”
Section: Methodsmentioning
confidence: 99%
“…16 Adult ticks were collected in October through December of 2008, 2010, and 2011, and during April and May in 2011, and March and April in 2012. Host-seeking nymphs were collected by the same procedure described for adult ticks during May and June 2008 from two locations in Fairfield, two locations in Middlesex, and three locations in New London Counties, Connecticut.…”
Section: Methodsmentioning
confidence: 99%
“…One especially problematic invasive plant in Connecticut is Berberis thunbergii (Japanese barberry). This perennial woody shrub provides excellent habitats for Lyme-disease carrying ticks thereby increasing the risk of infection in humans [12,13] in addition to altering ecosystem functions, such as nitrogen cycling, in invaded areas [14]. Japanese barberry was the second most frequently observed invasive plant at rare species sites in New England, and invasive plant presence was correlated with decreases in rare species population size [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, although there is phenomenological support for potential biotic effects of plant invasions on tick-borne disease risk mediated via tick hosts, mechanistic understanding has remained elusive. Studies conducted in the northeastern United States (31,32) have demonstrated that human risk of exposure to Lyme disease, which is caused by the bacterium Borrelia burgdorferi and transmitted by the black-legged tick (Ixodes scapularis), is increased by several exotic shrubs, including honeysuckle and Japanese barberry (Berberis thunbergii). The ecological mechanisms through which these plant invasions influence Lyme disease risk remain unknown, however, and an enhanced understanding of the mechanisms that drive disease risk is critical to mitigation and control strategies.…”
Section: Discussionmentioning
confidence: 99%